2014
DOI: 10.1161/jaha.114.001209
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Periesophageal Vagal Nerve Injury After Pulmonary Vein Antrum Isolation

Abstract: BackgroundPeriesophageal vagal nerve injury is recognized as a rare complication in atrial fibrillation ablation procedures. We investigated the factors associated with the occurrence of symptomatic periesophageal vagal nerve injury after pulmonary vein antrum isolation.Methods and ResultsOverall, 535 consecutive patients who underwent sole pulmonary vein antrum isolation were included. Point‐by‐point radiofrequency applications were applied using irrigated‐tip catheters under minimal sedation without esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
0
40
2
Order By: Relevance
“…Most recently, we demonstrated that AF ablation with a lower-energy setting of 20 W strictly controlled by esophageal temperature monitoring (ETM) at 39 °C could reduce the esophageal injury even in patients with a BMI<24.9 kg/m 2 [11] . As for the incidence of peri-ENI, Miyazaki et al reported that BMI was the only independent predictor for identifying patients who would develop peri-ENI during RF applications to the LA posterior wall with a relatively higher setting of 25–30 W and a duration of 30 s (OR=0.77; 95% CI=0.64–0.92; p =0.0045) [12] . However, data comparing the incidence of ETI (including esophageal injury and peri-ENI) following AF ablation with and without ETM are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, we demonstrated that AF ablation with a lower-energy setting of 20 W strictly controlled by esophageal temperature monitoring (ETM) at 39 °C could reduce the esophageal injury even in patients with a BMI<24.9 kg/m 2 [11] . As for the incidence of peri-ENI, Miyazaki et al reported that BMI was the only independent predictor for identifying patients who would develop peri-ENI during RF applications to the LA posterior wall with a relatively higher setting of 25–30 W and a duration of 30 s (OR=0.77; 95% CI=0.64–0.92; p =0.0045) [12] . However, data comparing the incidence of ETI (including esophageal injury and peri-ENI) following AF ablation with and without ETM are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative cardiac effects of vagal stimulation, namely bradycardia, have been reported during vagal schwannoma resection, although no case reports described lasting cardiac complications . Vagus nerve injury has been reported following cardiac procedures such as radiofrequency catheter ablation and pulmonary vein antrum isolation . Ablation has the potential to injure the vagus nerve at the level of the esophagus, causing dysphagia, heart burn, gastrointestinal reflux disease, nausea, bloating, early satiety, weight loss, constipation, diarrhea, and decreased gastric motility .…”
Section: Treatmentmentioning
confidence: 99%
“…Some reports suggest that these symptoms tend to resolve within 3‐6 months of the ablation procedure . Instances of periesophageal nerve injury have been associated with pulmonary vein atrium isolation procedures . In these cases, complications include gastric hypomotility, which tends to resolve over time …”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the development of upper gastrointestinal motility complications from injury to the vagus nerve and its branches has been described. 55,56 Thrombus formation. Coagulation and tissue necrosisinduced thermal energy in RF is associated with a risk of thrombus formation.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 99%